2014
DOI: 10.1111/acem.12317
|View full text |Cite
|
Sign up to set email alerts
|

Adult Scaphoid Fracture

Abstract: ObjectivesScaphoid fractures are the most common carpal fracture, representing 70% of carpal bone fractures. The diagnostic accuracy of physical examination findings and emergency medicine (EM) imaging studies for scaphoid fracture has not been previously described in the EM literature. Plain x‐rays are insufficient to rule out scaphoid fractures in a patient with a suggestive mechanism and radial‐sided tenderness on physical examination. This study was a meta‐analysis of historical features, physical examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 124 publications
2
63
1
5
Order By: Relevance
“…Annual incidence rates for all ages of 23-43 per 100,000 persons per year have been reported [7]. Scaphoid fractures are also problematic because diagnosis and treatment are difficult [8,9]. Scaphoid fractures are often complicated by non-union, osteonecrosis, tendon injuries and/or carpal tunnel syndrome, resulting in functional morbidity and eventual arthritic degeneration [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Annual incidence rates for all ages of 23-43 per 100,000 persons per year have been reported [7]. Scaphoid fractures are also problematic because diagnosis and treatment are difficult [8,9]. Scaphoid fractures are often complicated by non-union, osteonecrosis, tendon injuries and/or carpal tunnel syndrome, resulting in functional morbidity and eventual arthritic degeneration [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Scaphoid fractures are also problematic because diagnosis and treatment are difficult [8,9]. Scaphoid fractures are often complicated by non-union, osteonecrosis, tendon injuries and/or carpal tunnel syndrome, resulting in functional morbidity and eventual arthritic degeneration [7][8][9]. Additionally, presentation may be delayed when the injury is attributed to a wrist sprain instead of a more serious fracture event [10], resulting in higher levels of complications when treatment is commenced.…”
Section: Introductionmentioning
confidence: 99%
“…This review identified recent and consistent evidence to support the early use of MRI for suspected scaphoid fractures, as earlier confirmation of diagnosis contributes to reduced immobilisation time, healthcare utilisation and costs . An Australian pilot study in a regional ED setting supported these results, indicating that MRI within 1–3 days following the ED presentation dramatically reduced unnecessary immobilisation and time off work, time of treatment and healthcare usage in their setting, with better patient pain and satisfaction scores than controls .…”
Section: Discussionmentioning
confidence: 75%
“…In essence, a test does not add value to the care of the patient if neither a positive nor a negative test result will change the probability of a given diagnosis. Determining whether a diagnostic imaging test has the potential to affect estimates of disease probability requires knowledge not only of the test characteristics of the imaging modality, but also of the underlying pretest probability of disease, which depends on the diagnostic attributes of history, physical examination, and laboratory tests—parameters that are often understudied in ED settings …”
Section: The Value Of Imagingmentioning
confidence: 99%
“…Other examples from emergency medicine (EM) have been reported. Carpenter and colleagues investigated imaging for possible occult scaphoid fracture and determined that magnetic resonance imaging has the potential to change treatment if the pretest suspicion for fracture is above 0.4%, with a treatment threshold of 80%. Similarly, Taylor and Lalani identified that imaging has the potential to change management for suspected small bowel obstruction if the pretest probability is greater than 1.5%, with a treatment threshold for nasogastric intubation of 20.7%.…”
Section: The Value Of Imagingmentioning
confidence: 99%